ECONOMIC-STATISTICAL ANALYSIS OF THE ROLE OF THE SERVICE INDUSTRY IN THE COUNTRY'S ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: this article presents an economic and statistical analysis of the role of the service sector in the country's economy, an analysis of entities that create volumes in the service sector and operate in this sector, and an analysis of the dynamics of the development of the service sector in Uzbekistan. The analysis conducted shows, as just one example, that the number of private medical institutions in Uzbekistan is increasing day by day. This, in turn, creates healthy competition in the medical sector, which allows  improving  the  quality  of  medical  services  provided  to  the  population  and reducing  their  prices.  The  above  trends  are  reflected  in  the  fact  that  new  types  of services, especially those that are rapidly developing after the Covid-19 pandemic, are entering  the  Uzbekistan  market,  which  requires  special  attention  when  making decisions on economic development strategies, targeted programs and the development of the service sector.